The onset of cerebral infarction may be affected by differences in atmospheric pressure distribution patterns - Fukunaga, Atsushi; Koyama, Hideki; Fuse, Takahisa; Haraguchi, Asami (Frontiers in Neurology, 2023)
BACKGROUND: Some papers have highlighted a possible causal relationship between the onset of ischemic stroke and weather conditions. This study aimed to elucidate the onset mechanism of cerebral infarction from a meteorological approach. We focused on the atmospheric pressure distribution patterns (APDPs).The subjects are 221 cases diagnosed as cardiogenic cerebral embolism (Group A) and 612 cases diagnosed as atherosclerotic cerebral thrombosis (Group B). We investigated the APDP on the date closest to the date and time of onset of cerebral infarction in each patient on the website and chose the most similar one from the reported 11 APDPs. Groups A and B were compared for clinical characteristics and the appearance rate of each APDP in each group.The clinical characteristics of Groups A and B were consistent with some previously reported clinical characteristics of cerebral embolism and cerebral thrombosis except for smoking. The appearance rate of the other high-pressure type, which cannot be classified as either the anticyclone belt type or the migratory anticyclone type, in Group B was statistically significantly higher than that in Group A, and the appearance rate of the anticyclone belt type in Group A was statistically significantly higher than that in Group B (p < 0.05, Fisher's exact probability method, respectively).Cerebral embolism and cerebral thrombosis exhibited significant differences in APDPs on the day of onset. Dehydration particularly in the other high-pressure type or in the anticyclone belt type should be prevented. Further investigation should focus on the other meteorological factors.